2016
DOI: 10.18632/oncotarget.11814
|View full text |Cite|
|
Sign up to set email alerts
|

Discovery and clinical introduction of first-in-class imipridone ONC201

Abstract: ONC201 is the founding member of a novel class of anti-cancer compounds called imipridones that is currently in Phase II clinical trials in multiple advanced cancers. Since the discovery of ONC201 as a p53-independent inducer of TRAIL gene transcription, preclinical studies have determined that ONC201 has anti-proliferative and pro-apoptotic effects against a broad range of tumor cells but not normal cells. The mechanism of action of ONC201 involves engagement of PERK-independent activation of the integrated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
186
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 129 publications
(190 citation statements)
references
References 46 publications
1
186
0
3
Order By: Relevance
“…The compound is currently being tested in phase II clinical trials of patients with hematological malignancies and solid tumors (14,15). ONC201 was discovered in a phenotypic screen for compounds that could transcriptionally induce the TNF-related apoptosis inducing ligand ( TRAIL ) gene in colon cancer cells, independent of p53 status (16,17).…”
Section: Preclinical Activity Of Onc201 In Glioblastomamentioning
confidence: 99%
“…The compound is currently being tested in phase II clinical trials of patients with hematological malignancies and solid tumors (14,15). ONC201 was discovered in a phenotypic screen for compounds that could transcriptionally induce the TNF-related apoptosis inducing ligand ( TRAIL ) gene in colon cancer cells, independent of p53 status (16,17).…”
Section: Preclinical Activity Of Onc201 In Glioblastomamentioning
confidence: 99%
“…Early results from a Phase I clinical trial in advanced solid tumors demonstrated that ONC201 has a therapeutic PK profile, exceptional safety, induction of pharmacodynamics (PD) markers, and preliminary evidence of efficacy in various types of cancers. 8,9 Given the unique imipridone core, 10 we sought to explore chemical derivates of ONC201 to identify compounds with distinct therapeutic properties. We synthesized ONC201 analogs to identify compounds with distinct therapeutic properties that target ONC201-resistant tumor types or possess distinct signaling properties.…”
Section: Introductionmentioning
confidence: 99%
“…ONC201 is a member of a new class of anti-cancer compounds known as the imipridones [1]. ONC201 was originally identified as a p53-independent transcriptional inducer of TNF-related apoptosis inducing ligand (TRAIL) [2,3].…”
Section: Introductionmentioning
confidence: 99%